Ocular Drug Delivery Barriers-Role of Nanocarriers in the Treatment of Anterior Segment Ocular Diseases - Rinda Devi Bachu; Pallabitha Chowdhury; Zahraa H. F. Al-Saedi; Pradeep K. Karla; Sai H. S. Boddu (MDPI AG, 2018)
Ocular drug delivery is challenging due to the presence of anatomical and physiological barriers. These barriers can affect drug entry into the eye following multiple routes of administration (e.g., topical, systemic, and injectable). Topical administration in the form of eye drops is preferred for treating anterior segment diseases, as it is convenient and provides local delivery of drugs. Major concerns with topical delivery include poor drug absorption and low bioavailability. To improve the bioavailability of topically administered drugs, novel drug delivery systems are being investigated. Nanocarrier delivery systems demonstrate enhanced drug permeation and prolonged drug release. This review provides an overview of ocular barriers to anterior segment delivery, along with ways to overcome these barriers using nanocarrier systems. The disposition of nanocarriers following topical administration, their safety, toxicity and clinical trials involving nanocarrier systems are also discussed.